Nature‐inspired materials and designs for flexible lithium‐ion batteries. Issue 5 (18th May 2022) - Li, Heng; Wang, Huibo; Chan, Dan; Xu, Zhu; Wang, Kexuan; Ge, Mingzheng; Zhang, Yanyan; Chen, Shi; Tang, Yuxin
Abstract: Flexible lithium‐ion batteries (FLBs) are of critical importance to the seamless power supply of flexible and wearable electronic devices. However, the simultaneous acquirements of mechanical deformability and high energy density remain a major challenge for FLBs. Through billions of years of evolutions, many plants and animals have developed unique compositional and structural characteristics, which enable them to have both high mechanical deformability and robustness to cope with the complex and stressful environment. Inspired by nature, many new materials and designs emerge recently to achieve mechanically flexible and high storage capacity of lithium‐ion batteries at the same time. Here, we summarize these novel FLBs inspired by natural and biological materials and designs. We first give a brief introduction to the fundamentals and challenges of FLBs. Then, we highlight the latest achievements based on nature inspiration, including fiber‐shaped FLBs, origami and kirigami‐derived FLBs, and the nature‐inspired structural designs in FLBs. Finally, we discuss the current status, remaining challenges, and future opportunities for the development of FLBs. This concise yet focused review highlights current inspirations in FLBs and wishes to broaden our view of FLB materials and designs, which can be directly "borrowed" from nature. Abstract : Flexible lithium‐ion batteries (FLBs) are critical to the seamless power supply of emerging ﬂexible and wearable electronic devices. Recently, lent by inspiration from nature, various interesting FLBs with high mechanical deformability and energy density were developed. To this end, a focused review on the nature‐inspired materials and designs toward high‐performance FLB is given to guide future studies.